Teori Belajar dan Media Pembelajaran - Abdul Rahman; Nurraida Nurraida; Nurraini Nurraini (Pusat riset dan Inovasi Nasional, 2026)
This study examines the relationship between learning theories and the selection of instructional media in classroom practice. It is motivated by the observation that teachers often choose media based on availability rather than alignment with pedagogical goals. The purpose of this study is to analyze how behavioristic, cognitive, constructivist, and humanistic learning theories guide the design and use of effective instructional media. This research employs a qualitative approach using classroom observations, in-depth interviews with teachers and students, and document analysis. The findings indicate that instructional media aligned with learning theory significantly enhance students’ motivation, engagement, and comprehension. Interactive, student-centered media grounded in constructivist principles produced the strongest improvements, while drill-oriented media were most suitable for procedural skills. This study offers a practical model for aligning learning objectives, learning theories, and media selection that teachers can use in lesson planning.